ETIKA PEMBERITAAN PARTAI POLITIK DI TELEVISI (KASUS PEMBERITAAN PARTAI DEMOKRAT DI METRO TV DAN TV ONE) - Ali Mustofa (Jurnal Ilmiah Komunikasi Makna, 2012)
mass media news is essentially the construction of events by the mass media reality of what happened. The ability to construct this discourse will greatly affect the opinions, decisions and political attitudes readers. The whole process of production, distribution and consumption of communication message is the result of the interaction of the actors, consumers and distributors of communications. Interaction is what will inevitably put the communication process within the framework of human action. Where the action is good, where bad behavior. That is the main point of the ethical issues. Thus, the question raised is how the Ethics Democratic Political Coverage by Metro TV and TVOne station. This is because the Democratic Party on February 23, 2012 report on Metro TV and TVOne to the Indonesian Broadcasting Commission (KPI) for allegedly unbalanced coverage.